If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25.62 = 3.4x + 6 Reorder the terms: -25.62 = 6 + 3.4x Solving -25.62 = 6 + 3.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.4x' to each side of the equation. -25.62 + -3.4x = 6 + 3.4x + -3.4x Combine like terms: 3.4x + -3.4x = 0.0 -25.62 + -3.4x = 6 + 0.0 -25.62 + -3.4x = 6 Add '25.62' to each side of the equation. -25.62 + 25.62 + -3.4x = 6 + 25.62 Combine like terms: -25.62 + 25.62 = 0.00 0.00 + -3.4x = 6 + 25.62 -3.4x = 6 + 25.62 Combine like terms: 6 + 25.62 = 31.62 -3.4x = 31.62 Divide each side by '-3.4'. x = -9.3 Simplifying x = -9.3
| 1-2p+3=0 | | 5x=6x-6 | | -25.62=3.46+6 | | 4/5w=191/5 | | 1.5x+2x-.5=2.5x+x-.75 | | 2.7y+4.95=-0.72 | | 9x-(4x+6)=7x-20 | | 1/2(x+3)+6x=1/3(12x+3) | | -6x/5= | | 11x+4=7x-12 | | -11.15=15.1-3.5y | | 4(a+2)+1=7a-3(a-2) | | 5-11x=105 | | 11x+4=7z-12 | | 2-2.2y=-12.3 | | 77=35x | | 1/4(2x-9)=8 | | 37=5a-5a-3 | | 3.8x+87=5.3x+36 | | y-8+3y+2=-98 | | 6y-9-y-8= | | 1.3x=11.7 | | (-2.5)m-3.2=74.1 | | 8.0c+8=2.7c+33.97 | | 35=25x/6 | | (2/(x+2))+(3/(x-1))=-(8/5) | | 0.5(8x+4)-(x+7)= | | 1/2(48+24b)=2(17-4b) | | 1/5x+5=19-1/2 | | 12x^2+20+3=0 | | 11x+4=7x-11 | | 4.4+1.5n=0.80 |